Estimation Distributed Algorithm to Aid Aircraft Runway Scheduling Problem - Liu, Yingli; Hu, Minghua; Su, Jiaming (Journal of physics. Conference series, 2023)
In this paper, we proposed a runway sequencing and optimal scheduling method. This includes constructing a flight sequencing model to minimize design delay time for arrival and departure flights and designing flight sequencing rules to obtain large-scale feasible runway usage sequences efficiently. Furthermore, a Kendall- τ distance-based Mallows model is constructed based on the obtained flight sequences. An Estimation Distributed Algorithm (EDA) is used to assign each flight a runway usage time that meets the constraint so that the total delay time is minimized. Finally, it is verified that the method can not only reduce the total delay time of the flight as a whole but also has significant performance and is highly implementable through the analysis of calculation cases.